“Defined Spaces” in the Literary-Historical Discourse of the Novel “The Rebels” by Vincas Mykolaitis-Putinas - Jakaitė, Dalia (Acta humanitarica academiae Saulensis, 2024)
The novel “The Rebels” (Sukilėliai) by Vincas Mykolaitis-Putinas was written, edited and unfinished for more than a decade in a historically-ideologically complicated time (~ 1953–1967), almost until the death of the writer. Both the novel and the writing Material written around 1953–1960, which have so far not received the attention of researchers, have not only traces of Soviet-era ideology, but also imprints of authentic historical memory. Bearing in mind the importance of a certain region or specific localities in general in the reception of the uprising of 1863–1864, it is worth taking a fresh look at this aspect in “The Rebels” by Mykolaitis-Putinas, to make an assumption about the meaning of the place and its images in the concept of the novel.The object of the article is the literary-historical discourse characterized by the memory of specific places, localities or wider territories, countries or ethnographic regions in the novel by Mykolaitis-Putinas and in the Material (additional resource). This discourse is considered to be literary, folkloric, partly also religious intertexts in the research sources, the cultural memory of the uprising characterized by images of places and regions. Methodologically, the research is based on the concept of cultural and social memory. Without bypassing the controversial reception of “The Rebels”, the literary-historical significance of the novel and its wider context is shown by examining such semantic lines as the unity of Lithuanians with Poles, the rebels’ hostility to the maskoliai, the mythologisation of the uprising, the religious narrative, etc.
Keywords: novel; uprising; place; memory; aspect; Vincas Mykolaitis-Putinas